When capital loses its green makeup. The impact of biodiesel production on Santiago del Estero Province, Argentina - Toledo López, Virginia (Sociedade & Natureza, 2020)
The article analyses the environmental management of biodiesel production in Santiago del Estero Province, Argentina, focusing on the treatment of effluents. Therefore, using a qualitative methodology, this article studies the main actors’ repertoires concerning their territorial strategies. The production of biodiesel is considered a reaffirmation of the agribusiness expansion in the area and its environmental impact as forms of dispossession of the inhabitants. The study shows that the practices of hegemonic actors are associated with a non-preventive and standard approach to environmental issues, even when they use the ecological modernization frame through the Corporate Social Responsibility. Finally, it reflects on a positive effect of environmental conflicts in the territory.